Electrical and Mechanical Characteristics of a High-Speed Motor for Electric Turbochargers in Relation to Eccentricity - Tae-Woo Lee; Do-Kwan Hong (Energies, 2021)
As the demand for eco-friendly, high-efficiency transportation technologies increase due to climate change, a high-speed electric motor, a key component of an electric turbocharger, has been developed that can reduce emissions and increase fuel efficiency. Korea Electrotechnology Research Institute with Keyyang Precision Co., Ltd., developed a high-speed surface-mounted permanent magnet synchronous motor. It operates at a power of 3 kW at 100,000 rpm and is intended to fit 1600 cc diesel vehicles. In this paper, the electrical and mechanical characteristics of the high-speed motor were reviewed in consideration of the effect of eccentricity among the various causes that affect vibration. It was confirmed that eccentricity affected the distribution of the electromagnetic force and inductance of the winding due to the uneven air-gap. Additional vibration was generated at the half of pole passing frequency (1666.67 Hz). Diagnosing the presence or absence of eccentricity when driving a motor takes a great deal of time and cost because the load is separated or the motor is diagnosed through disassembly and measurement. The characteristics of eccentricity identified in this paper can be checked using a relatively simple method when diagnosing the presence or absence of actual eccentricity.